2002
DOI: 10.1016/s0886-3350(02)01452-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of intraocular lenses in eyes with cataract and uveitis

Abstract: Phacoemulsification with IOL implantation in selected uveitic eyes was safe and effective. Acrylic IOLs provided a better visual outcome and lower complication rate than IOLs of other materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 32 publications
4
99
0
3
Order By: Relevance
“…This confirms previous observations [10]. Alio et al reported the presence of synechiae, especially in eyes with silicone IOLs [7]. In the study of Rauz et al, significant posterior synechiae were also noted in patients with acrylic IOLs [12].…”
Section: Influence On Uveal Biocompatibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms previous observations [10]. Alio et al reported the presence of synechiae, especially in eyes with silicone IOLs [7]. In the study of Rauz et al, significant posterior synechiae were also noted in patients with acrylic IOLs [12].…”
Section: Influence On Uveal Biocompatibilitysupporting
confidence: 88%
“…Schauersberger et al did not observe significant numbers of small round cells on any IOLs in a group of patients without uveitis [9], nor did Alio et al find significant differences in small round cell or giant cell deposition between hydrophobic acrylic, silicone, or PMMA IOLs in patients with a history of uveitis [7]. However, hydrophobic and hydrophilic IOLs were not separately analyzed.…”
Section: Influence On Uveal Biocompatibilitymentioning
confidence: 99%
“…In this series these trends have been reinforced; no IOL required removal or exchange after a minimum of 5 years; none has been significantly decentred; and the number compromised by adherent inflammatory cells has been small. The optimal IOL material is the continued subject of debate, 31,[34][35][36] and long-term follow-up studies such as this cannot address such issues (being intrinsically out of date with developments in materials). Nevertheless, the high degree of long-term intraocular tolerance of PMMA IOLs, with or without HSM, is further encouragement to the almost universal use of IOLs in patients with uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of intraocular lens type, silicone, acrylic and hydrogel lenses may be used but a possible advantage has been shown for acrylic lenses, which may cause less post-operative inflammation and posterior capsular opacification. 70 Post-operatively, patients may require more intensive topical steroid or other immunomodulatory therapy for control of inflammation.…”
Section: Uveitismentioning
confidence: 99%